Clinical frailty and functional trajectories in hospitalized older adults: a retrospective observational study - Romero-Ortuno, Roman (My University, 2017)
Frailty predicts inpatient mortality and length of stay, but its link to functional trajectories is under-researched. Addenbrooke's Hospital, Cambridge, UK, collects the Clinical Frailty Scale (CFS) within 72 h of admission for those aged ≥75 years. We studied whether the CFS links to functional trajectories in hospitalized older adults. Methods: This was a retrospective observational study in an English university hospital. We analyzed all first episodes of county residents aged ≥75 years admitted to the Department of Medicine for the Elderly wards between December 2014 and May 2015. Data were extracted from the hospital's information systems. Patients were classified as non-frail (CFS 1–4), moderately frail (CFS 5–6) and severely frail (CFS 7–8). Function was retrospectively measured with the modified Rankin Scale (mRS) at preadmission, admission and discharge. Results: Of 539 eligible patients, 46 died during admission (mortality rates: 2% in CFS 1–4, 5% in CFS 5–6, 19% in CFS 7–8). Among the 493 survivors, 121 were non-frail, 235 moderately and 137 severely frail. The mean mRS of the non-frail was 1.8 (95% CI 1.7–2.0) at baseline, 3.3 (95% CI 3.1–3.5) on admission and 2.2 (95% CI 2.0–2.3) on discharge (mean length of stay 9 days). The moderately frail had a mean mRS of 2.9 (95% CI 2.8–3.0) at baseline, 4.0 (95% CI 3.8–4.1) on admission and 3.2 (95% CI 3.1–3.3) on discharge (mean length of stay 15 days). The severely frail had mean mRS of 3.5 (95% CI 3.3–3.6) at baseline, 4.3 (95% CI 4.1–4.4) on admission and 3.7 (95% CI 3.6–3.9) on discharge, respectively (mean length of stay 17 days). Conclusions: In older inpatients, frailty might be linked to lower and slower functional recovery. Prospective work is required to confirm these trajectories and understand how to influence them.
PUBLISHED
Keywords: frailty; Clinical Frailty Scale (CFS); functional trajectories; frailty; Clinical Frailty Scale (CFS); functional trajectories; Ageing